Application of The Discussion Method with The Problem Based Learning Model in Increase Results Study Student Class VII School PAI Subject Negeri 1 East Solor - Nuraini, Siti; Sholihuddin, Ahmad; Wahyuni, Sri; Ningrum, Ary Setya Budhi; Ika Setiyarini (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
The conditions above clearly result in maximum student learning outcomes not being achieved due to students` lack of understanding of the material that has been provided. 2. How to use the Discussion Method with the Problem Based Learning learning model able to increase students' learning motivation? 3. How to use the Discussion Method with the Problem Based learning model Learning is able to provide a better level of understanding of the material (learning outcomes) than The type of research in this research is Classroom Action Research. Education and Humans cannot be separated from life, whether family, society as well as nation and state, this is as stated in Republic of Indonesia Law Number 20 of 2003 concerning the National Education System, namely: “Education is a conscious and planned effort to create a learning atmosphere and the learning process so that students actively develop their potential himself to have religious spiritual strength, self-control, personality, intelligence, noble morals, and skills needed by himself, society, race and country``. Education and Humans cannot be separated from life, whether family, society as well as nation and state, this is as stated in Republic of Indonesia Law Number 20 of 2003 concerning the National Education System, namely: “Education is a conscious and planned effort to create a learning atmosphere and the learning process so that students actively develop their potential himself to have religious spiritual strength, self-control, personality, intelligence, noble morals, and skills needed by himself, society, race and country``. The problem -based learning model is becoming a problem the challenge of whether his presence will have a positive impact on change The conditions above clearly result in maximum student learning outcomes not being achieved due to students` lack of understanding of the material that has been provided. 2. How to use the Discussion Method with the Problem Based Learning learning model able to increase students' learning motivation? 3. How to use the Discussion Method with the Problem Based learning model Learning is able to provide a better level of understanding of the material (learning outcomes) than The type of research in this research is Classroom Action Research. Education and Humans cannot be separated from life, whether family, society as well as nation and state, this is as stated in Republic of Indonesia Law Number 20 of 2003 concerning the National Education System, namely: “Education is a conscious and planned effort to create a learning atmosphere and the learning process so that students actively develop their potential himself to have religious spiritual strength, self-control, personality, intelligence, noble morals, and skills needed by himself, society, race and country``. Education and Humans cannot be separated from life, whether family, society as well as nation and state, this is as stated in Republic of Indonesia Law Number 20 of 2003 concerning the National Education System, namely: “Education is a conscious and planned effort to create a learning atmosphere and the learning process so that students actively develop their potential himself to have religious spiritual strength, self-control, personality, intelligence, noble morals, and skills needed by himself, society, race and country``. The problem -based learning model is becoming a problem the challenge of whether his presence will have a positive impact on change The conditions above clearly result in maximum student learning outcomes not being achieved due to students` lack of understanding of the material that has been provided. 2. How to use the Discussion Method with the Problem Based Learning learning model able to increase students' learning motivation? 3. How to use the Discussion Method with the Problem Based learning model Learning is able to provide a better level of understanding of the material (learning outcomes) than The type of research in this research is Classroom Action Research. Education and Humans cannot be separated from life, whether family, society as well as nation and state, this is as stated in Republic of Indonesia Law Number 20 of 2003 concerning the National Education System, namely: “Education is a conscious and planned effort to create a learning atmosphere and the learning process so that students actively develop their potential himself to have religious spiritual strength, self-control, personality, intelligence, noble morals, and skills needed by himself, society, race and country``. Education and Humans cannot be separated from life, whether family, society as well as nation and state, this is as stated in Republic of Indonesia Law Number 20 of 2003 concerning the National Education System, namely: “Education is a conscious and planned effort to create a learning atmosphere and the learning process so that students actively develop their potential himself to have religious spiritual strength, self-control, personality, intelligence, noble morals, and skills needed by himself, society, race and country``. The problem -based learning model is becoming a problem the challenge of whether his presence will have a positive impact on change